Analysis of Stock Prices: A Case Study of Indonesia Stock Exchange - Suryana, (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to examine the effect of bankruptcy predictions by the Altman Z-Score formulas on stock prices. This research was conducted on the basis of the phenomenon of retail companies throughout the period 2013-2017. This type of research is causal explanatory. The research population is 21 retail companies. The results showed that the prediction of bankruptcy using the Altman Z-score formulas had a significant effect on stock prices in retail companies